2012
DOI: 10.5301/jva.5000068
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of StarClose SE Vascular Closure System in High-Risk Liver Interventional Oncology Patients

Abstract: Purpose To assess the safety and efficacy of the StarClose SE Vascular Closure System (Abbott Vascular, Abbott Park IL, USA) in high-risk thrombocytopenic and coagulopathic interventional oncology (IO) patients. Methods In this single institution retrospective study, 63 high-risk thrombocytopenic or coagulopathic IO patients (M:F=51:12, mean age 58 years, range 31–88 years) who underwent 83 common femoral arteriotomy closures using the StarClose device were identified among all IO patients (n=131) undergoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…For example, McTaggar et al [ 10 ] used StarClose in 281 patients undergoing interventional surgery and found that the incidence of self-limiting hematoma was the highest, and no patients had other/minor complications. Gaba et al [ 11 ] observed 83 patients with liver tumors using StarClose vascular closure device as interventional treatment and found that only three (3.6%) developed small inguinal hematomas after the operation. The least common complication of the vascular closure device was acute limb ischemia, vascular stenosis or occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…For example, McTaggar et al [ 10 ] used StarClose in 281 patients undergoing interventional surgery and found that the incidence of self-limiting hematoma was the highest, and no patients had other/minor complications. Gaba et al [ 11 ] observed 83 patients with liver tumors using StarClose vascular closure device as interventional treatment and found that only three (3.6%) developed small inguinal hematomas after the operation. The least common complication of the vascular closure device was acute limb ischemia, vascular stenosis or occlusion.…”
Section: Discussionmentioning
confidence: 99%